Designing a Web-Based Digital Certificate Application Using the Waterfall Method - susannaiyah, lucy; Darujati , Cahyo (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
In the digital era that continues to develop, information technology has brought many aspects of life, including managing activity certificates in educational and professional environments. Activity certificates have an essential role in recognizing participants. Built using the Laravel framework and the PHP programming language, this application features easy public access to certificates via online links. Thus, this research aims to design a digital certificate application that is effective and easy to use, hoping that it can positively contribute to DIGITAL-ID AKADEMI in improving the quality of services and management of activities. The issuance and distribution of certificates will positively impact Digital's reputation. ID ACADEMI is an innovative educational institution that is responsive to technological developments.